Enhancement mechanism of magnetite on the ball-milling destruction of perfluorooctane sulfonate by iron. (15th February 2023) - Hu, Jun; Qiu, Yifan; Gu, Bing; Yao, Nv; Lou, Zimo; Cheng, Zhuowei; Zhang, Xianzhao; Yu, Jianming
Abstract: Zero-valent iron (Fe) is commonly employed as an additive for the mechanochemical destruction (MCD) of organic pollutants. The poly- and perfluoroalkyl substances (e.g., perfluorooctane sulfonate, PFOS) are a class of toxic environmental pollutants that are difficult to effectively degrade due to their thermodynamic and chemical stability. In this study, magnetite (Fe3 O4 ) was applied to improve the milling performance of Fe to PFOS and its promoting mechanisms were emphatically explored. The desulfurization rate was in ahead of the defluorination rate because the C–S bond is less stable than the C–F bonds in PFOS. Fe3 O4 had an excellent reinforcement effect on the milling performance of Fe, which was mainly through accelerating the electron transfer as a conductor, reacting with Fe to produce FeO, and facilitating the formation of HO ● . During the MCD of PFOS with Fe/Fe3 O4 as an additive, HO ● played a dominant role in the defluorination process (accounting for >67%). After the elimination of sulfonate group (−SO3 − ), the produced radical (C7 F15 CF2 ● ) continued to react through two main pathways: one was the stepwise defluorination after hydrogenation, and the other one was oxidation reaction after alcoholization to yield the corresponding aldehydes and carboxylic acids. The optimum Fe fraction (MFe ) was 30%, and air atmosphere was more effective than oxygen and nitrogen conditions. This study helps to comprehensively understand the role of Fe3 O4 in defluorination and fills the gap of Fe/Fe3 O4 application in the MCD of PFASs. Graphical abstract: Image 1 Highlights: Fe3 O4 improved the milling performance of Fe to perfluorooctane sulfonate. Fe3 O4 was beneficial to the electron transfer, FeO formation and HO. ● production. Two reaction pathways of the formed radicals after desulfurization were proposed. Fe3 O4 fraction and atmospheric condition influenced milling performance.